The Effect of Liquidity and Leverage on Tax Aggressiveness. Case Studies on Manufacturing Companies in the Food and Beverage Industry Sector Listed on the Indonesian Stock Exchange for the 2019-2021 Period - Istiyanatul Mahbubah; Annisa Zhafarina Qosasi (Technium Social Sciences Journal, 2023)
Tax aggressiveness as an action that aims to reduce the tax burden through tax planning using methods that are or are not classified as tax violations (Hadi & Mangoting, 2014). Richardson and Lanis (2012) define tax aggressiveness as the desire and action to minimize the tax burden by means of legal, illegal, or both. The first factor that can influence corporate tax aggressiveness is liquidity. Liquidity is the ability of a company to fulfill its short-term obligations which must be paid immediately in one period or less by using its current assets. Tax is one part of the company’s short-term obligations. In addition, a company’s financial decisions which are explained by the company’s leverage ratio are also predicted to have a significant effect on the emergence of tax aggressiveness. The higher the leverage of a company, the higher the company’s dependence on asset financing through debt and loans or loans to companies that have a fixed burden in the form of interest expenses. This type of research is quantitative research, where data is presented in the form of numbers and can be measured and tested using statistical methods. The data used in this study is data on the annual financial reports of manufacturing companies in the food and beverage sub-sector that are listed on the Indonesia Stock Exchange (IDX) for 2019-2021. Of the entire population, there were 21 companies that met the criteria used as samples, the data obtained from the nine companies totaled 63 data.